Blockchain-Assisted Trustworthy QoE Accelerator for Adaptive Streaming Over HTTP - Jeongjin Park; Gi Seok Park (IEEE Access)
This paper presents a blockchain-assisted trustworthy quality of experience (QoE) accelerator for adaptive streaming services over hypertext transfer protocol (HTTP). The proposed trustworthy QoE accelerator aims to provide seamless, energy-efficient, and trustworthy streaming services to mobile users. The proposed QoE accelerator is logically located in the middle of the path between the mobile user and media server. At the midpoint, the accelerator severs the end-to-end transmission control protocol (TCP) connection and establishes parallel HTTP connections with the media cloud. Then, the accelerator appropriately assigns segment requests to each parallel stream to make effective use of network resources. Further, a blockchain network is utilized to make the proposed system trustworthy. To demonstrate the potential for real-world deployment, the proposed blockchain-assisted QoE accelerator was implemented using the moving picture experts group (MPEG) DASH open-source player, Hyperledger Fabric open-source blockchain, Docker, and Kubernetes and thoroughly verified using the 802.11 network. The experimental results showed that the blockchain-assisted QoE accelerator outperforms existing approaches in terms of QoE metrics such as frozen events and temporal video quality.